DIGITAL WATERMARKING AS CONTENT PROTECTION SCHEME - Santoso, Petrus (Institute of Research and Community Outreach, 2004)
Nowadays, as the Internet grows rapidly, the copyright laws are not effective anymore, since a lot of copyrighted products (picture, audio, video, document, etc.) are available as digital data. Any unauthorized parties able to produce identical copies of digital data without degrading the original contents and to distribute the copies over the network. This condition has led to a strong demand for reliable and secure distribution of digital data over networks. Such a technique developed to overcome this problem is digital watermarking. Digital watermarking is a process in digital domain, which embeds a watermark into a copyrighted digital data, to protect its value, so that it cannot be used by unauthorized parties. This paper is intended to give an overview on digital watermarking. First, three application fields of watermarking are described and illustrated with some scenarios, namely watermarking for copyright protection, watermarking for copy protection, and watermarking for image authentication. Then watermarking techniques are discussed, starting from the basic watermarking procedure, followed by review of some watermarking techniques. And later, some attacks and obstacles to watermarking are highlighted. In conclusion, digital watermarking technology plays important role in content protection issues. Attacks and obstacles are also had to be faced by this technology. The main obstacle is that there is no standard available for watermarking techniques. Without any specific standard, it is difficult to determine how robust a watermarking technique should be.